Modeling, Simulation and Extraction of Model Parameters of Dye-Sensitized Solar Cells (DSSCs) using Different Single-Diode Models - Yerima, Jamu Benson; William, Dunama; Babangida, Alkali; Ezike, Sabastine Chinedu (Computational And Experimental Research In Materials And Renewable Energy, 2023)
Modeling, simulation and extraction of model parameters of four DSSCs was carried out using four different models. The results show that model parameters depend on of the types of models and dyes (or DSSCs). Also, the fewer the number of model parameters the lesser the computation efforts and knowledge about the internal features of the photovoltaic system and vice versa. In addition, the photocurrent Iph of a DSSC is constant for all models. Furthermore, the diode reverse saturation current Io is inversely proportional to the absolute values of the series resistance Rs and shunt resistance Rsh. Moreover, the modified diode ideality factor depends on the number of model parameters and nature of dye/DSSC. However, models with higher number of model parameters (4 and 5) involving resistances manifest parameter irregularity. Nevertheless, the negative sign or complexity of the model parameters does not render them undesirable elements for researchers to use them in their application. Thus, the overall result shows that all the models used produced good I-V curve fit for all the solar cells studied irrespective of the presence of parameter irregularity.Keywords: Modeling, Simulation, Model parameter, DSSCs, Single diode model, Parameter irregularity.